A Multifunctional Metal–Phenolic Nanocoating on Bone Implants for Enhanced Osseointegration via Early Immunomodulation - Jin Liu; Yilin Shi; Yajun Zhao; Yue Liu; Xiaoru Yang; Kai Li; Weiwei Zhao; Jianmin Han; Jianhua Li; Shaohua Ge (Advanced Science, 2024)
Abstract Surface modification is an important approach to improve osseointegration of the endosseous implants, however it is still desirable to develop a facile yet efficient coating strategy. Herein, a metal–phenolic network (MPN) is proposed as a multifunctional nanocoating on titanium (Ti) implants for enhanced osseointegration through early immunomodulation. With tannic acid (TA) and Sr2+ self‐assembled on Ti substrates, the MPN coatings provided a bioactive interface, which can facilitate the initial adhesion and recruitment of bone marrow mesenchymal stem cells (BMSCs) and polarize macrophage toward M2 phenotype. Furthermore, the TA‐Sr coatings accelerated the osteogenic differentiation of BMSCs. In vivo evaluations further confirmed the enhanced osseointegration of TA‐Sr modified implants via generating a favorable osteoimmune microenvironment. In general, these results suggest that TA‐Sr MPN nanocoating is a promising strategy for achieving better and faster osseointegration of bone implants, which can be easily utilized in future clinical applications.